Influence of childhood asthma on dental caries: A longitudinal study - Tomi Samec; Bennett Tochukwu Amaechi; Janja Jan (Wiley, 2021)
Abstract Objectives The study investigated the influence of childhood asthma on dental caries development and caries risk factors among children with asthma in Slovenia. Material and methods The study population consisted of 2-17 years old children (n = 138), who had used anti‐asthmatic medicines for at least 1 year. Controls were their non‐asthmatic siblings (n = 140). International Caries Detection and Assessment System‐II was used to assess caries status. After 3 years, 106 baseline participants (53 asthmatic and 53 siblings) were reexamined. Questionnaires completed by parents and data from the patients' medical records provided information on demographics, child's medical history, medication usage, and oral health behaviors. Additional 308 asthmatic children were examined to assess caries risk factors among children with asthma. Results Asthmatic children had significantly higher mean d12fs and D12MFS (p ≤ 0.05), and fewer caries‐free individuals (p ≤ 0.01). In asthmatic children, 3 years mean increment in D12MFS was significantly higher (p ≤ 0.05). Furthermore, progression over 3 years from sound tooth surfaces to decayed cavitated and filled lesions in primary and permanent teeth were present in significantly higher (p ≤ 0.05) percentage, and likewise transition from decayed cavitated lesions to missing tooth surfaces because of caries in primary teeth, and from filled to filled non‐cavitated and cavitated lesions in permanent teeth. Lower caries experience in asthmatic children was associated with lower doses of inhaled glucocorticoid use, leucotriene antagonist use, and daily milk and cheese consumption. Conclusions Asthmatic children who had used anti‐asthmatic medicines had higher caries experience and higher caries progression over 3 years in both primary and permanent dentitions. Besides anti‐asthmatic medicines, other factors were associated with higher caries experience in asthmatic children.